The Relevance of Perpetual Peace in Henry van Dyke’s Ashes of Vengeance - Putriana, Kadek Olivia Novi; Zaky, Raffi Ahmad; Hamdani, Farham Nazhib; Salsabila, Anindya Thalita; Pasopati, Rommel Utungga (SALIENCE: English Language, Literature, and Education Journal, 2024)
This paper explores the concept of perpetual peace in Henry van Dyke's flash fiction entitled Ashes of Vengeance. The story revolves around the harsh city of Dun, where a man, known as the avenger, seeks revenge for the death of his family. He escapes prison and offers a secret pathway to take over the city to the chief of the besiegers, Alaric. However, upon seeing the city's current state, he changes his focus to peace. Then, how is perpetual peace related in Henry van Dyke’s Ashes of Vengeance? Through Immanuel Kant's theory of perpetual peace, stable peace occurs when all people, governed by universal rule of law, rather than proprietary rulers. In this story, the proprietary ruler is represented by the people of Dun, while Alaric represents the person who wishes to rule according to universal law. Using qualitative analysis, the paper concludes that individuals can achieve stable peace if people do not commit an act that would make a possibility of peace impossible for the future, and that perpetual peace will gradually be achieved.